Endovascular Rescue Treatment for Delayed Cerebral Ischemia After Subarachnoid Hemorrhage Is Safe and Effective - Weiss, Miriam; Conzen, Catharina; Mueller, Marguerite; Wiesmann, Martin; Clusmann, Hans; Albanna, Walid; Schubert, Gerrit Alexander (Frontiers in Neurology, 2019)
Background: The implementation of rescue efforts for delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage remains largely empirical for a lack of supporting evidence, while the associated risk profile is also unclear. Objective: The present study evaluates the safety and efficacy of endovascular rescue treatment (ERT: continuous intraarterial nimodipine, IAN; transcutaneous balloon angioplasty, TBA). Methods: In this prospective observational study, we assessed periprocedural complications and side effects in context of ERT. We evaluated neurological status, multimodal neuromonitoring (ptiO2, lactate/pyruvate ratio, transcranial doppler) and cranial imaging (CTP, DSA). All parameters were included into multivariate analysis to determine predictors for the need of retreatment. Results: We included 33 consecutive patients with 54 ERT (IAN n=35; TBA n=13; TBA+IAN n=6). We recorded no serious complications and initial improvement in all parameters (neurostatus 72.3% of patients; ptiO2 15.0±11.7 to 25.8±15.5, p<0.0001; lactate/pyruvate ratio 46.3±27.5 to 31.0±9.7, p<0.05; transcranial doppler 139.0±46.3 to 98.9±29.6, p<0.05; CTP 81.6% of patients; DSA 93.1% of patients). Retreatment (n=16, 48.5%) was independently associated with preinterventional ptiO2<5mmHg (p<0.01) and early (<72hours) discontinuation of IAN treatment (p=0.08). DCI related cerebral infarction was noted in n=8 patients (24.2%). At three months after discharge, favorable outcome was noted for n=11 (35.5%) patients. Conclusion: Provided a detailed decision tree, timely ERT can provide a relatively safe and effective treatment option in those highly-selected patients undergoing multimodality monitoring where conservative treatment options are exhausted. Continuous treatment in particular may be suitable to surpass sustained DCI and was associated with a low rate of DCI related infarction and comparably high percentage of good outcome.